Incorporation Mechanism of Potassium in FAPbI3 Perovskite Solar Cell Materials - Alevli, M.; Gungor, N.; Kavak, P.; Sahin, N.; Corcor, A.; Topal, I.; Esmer, K.; Cakmakci, E.; Deger, C.; Yavuz, I. (AMER CHEMICAL SOC, 2024)
We study the structural and electronic mechanisms of potassium (K+) incorporation in the FAPbI(3) perovskite layer. The K+ ions in FAPbI(3) perovskite solar cells lead to higher power conversion efficiency (PCE), lower trap density, and faster charge transfer. K+ eliminates the I-V hysteresis for 5% K-doped perovskite. Moreover, the phase stability is reduced by K+ incorporation. The enhancement in PCE and reduced stability are attributed to the passivation of deep-level charge traps and increased carrier mobility and lower phase change activation energy, respectively, and in all cases, K-FA antisite formation is revealed, by density functional theory (DFT) calculations, to be the main source. K-FA has reduced the electron-phonon coupling of charge transport and the activation energy barrier for the cubic-to-hexagonal phase transformation, which accelerates phase degradation. Our key findings will enable the future design and optimization of high-efficiency and stable mixed-perovskite solar cells.
Keywords: TOTAL-ENERGY CALCULATIONS; HALIDE PEROVSKITES; HYSTERESIS; EFFICIENT; FILMS; Chemistry; Science & Technology - Other Topics; Materials Science